The Application of a Contact Lens Sensor in Detecting 24-Hour Intraocular Pressure-Related Patterns - Sarah C. Xu; Angela C. Gauthier; Ji Liu (Journal of Ophthalmology)
Glaucoma is one of the leading causes of blindness worldwide. Recent studies suggest that intraocular pressure (IOP) fluctuations, peaks, and rhythm are important factors in disease advancement. Yet, current glaucoma management remains hinged on single IOP measurements during clinic hours. To overcome this limitation, 24-hour IOP monitoring devices have been employed and include self-tonometry, permanent IOP, and temporary IOP monitoring. This review discusses each IOP measuring strategy and focuses on the recently FDA-approved contact lens sensor (CLS). The CLS records IOP-related ocular patterns for 24 hours continuously. Using the CLS, IOP-related parameters have been found to be associated with the rate of visual field progression in primary open-angle glaucoma, disease progression in primary angle-closure glaucoma, and various clinical variables in ocular hypertension. The CLS has been used to quantify blink rate and limbal strain and measure the circadian rhythm in a variety of disease states including normal-tension glaucoma and thyroid eye disease. The effects of various IOP-lowering interventions were also characterized using the CLS. CLS provides a unique, safe, and well-tolerated way to study IOP-related patterns in a wide range of disease states. IOP-related patterns may help identify patients most at risk for disease progression and assist with the development of tailored treatments.